ANALISIS PENYUSUNAN DAN PELAKSANAAN ANGGARAN BELANJA PADA KANTOR KECAMATAN KELAPA LIMA - Anggi Lalita D. Salmon; Thobias E.D. Tomasowa; Rosdiana Mata (P3M- Politeknik Negeri Kupang, 2021)
A budget is a future financial plan containing estimates of revenue and expenditure to be implemented in a specific time period. This study aims to determine budget preparation in Kelapa Lima District in accordance with Permendagri Number 21 of 2011 concerning the second amendment to Permendagri Number 13 of 2006 concerning Guidelines for Regional Financial Management and to determine the effectiveness of budget implementation from 2017 to 2019. The writer's research method is descriptive qualitative by collecting interview data and documentation from the research location. The budget preparation analysis step is to collect data and compare it with the budget preparation guidelines, and based on the results of these comparisons; conclusions will be drawn. The step of analyzing the effectiveness of budget execution is calculating the effectiveness based on the realization against the budget, seeing the effectiveness achievement according to the criteria, and drawing conclusions. The results of this study indicate that Kelapa Lima District, as SKPD has prepared a budget according to Permendagri No. 21 of 2011. Kelapa Lima District is also considered to have carried out effectiveness in implementing the expenditure budget. Even though expenditure was included in the effective criteria in 2017 and 2018 and was quite effective in 2019, the realization of the expenditure achieved still did not meet the set budget target. It happened due to expenditures that have not been used up